Subperceptional Burst Versus Perceptional Tonic Spinal Cord Stimulation Waveforms for Drug‐resistant Orthostatic Tremor: Comparative Data of 2 Cases. Issue 4 (3rd April 2017) - Pintea, Bogdan; de Boni, Laura; Kinfe, Thomas M.
Abstract: Background: Spinal cord stimulation (SCS) and deep‐brain stimulation reportedly improve refractory orthostatic tremor (OT). No comparative data exist assessing subperceptional versus perceptional SCS with sham stimulation in patients with OT. Methods: Two patients who had refractory OT were assessed at baseline and 3 months after SCS implantation using 3 different SCS modes: paraesthesia‐free burst SCS (40 Hz), sham SCS, and paraesthesia‐evoking tonic SCS (100–130 Hz). Surface electromyography, standing time, stimulation parameters, and any adverse events were prospectively recorded. Results: Improved standing time was observed under burst and tonic mode versus stimulation off and compared with baseline in both patients (patient 1: baseline = 22‐second; burst SCS [subperceptional]/ standing time = 2.8 minutes; stimulation off/ standing time = 28 seconds; and tonic SCS [perceptional]/ standing time = 1.2 minutes; patient 2: baseline = 47‐second; burst SCS [subperceptional]/ standing time = 3.1 minutes; stimulation off/ standing time = 48 seconds; and tonic SCS [perceptional]/ standing time = 1.1 minute). The electromyography frequency demonstrated a decline in tremor frequency. Conclusion: Burst as a novel SCS paradigm may be co‐considered in patients with refractory OT before more invasive deep‐brain stimulation.